Analysis of SNP haplotypes - Palmer, Lyle (Henry Stewart Talks, 2007)
Phenotype-genotype association, Linkage disequilibrium maps and allelic association, What is linkage disequilibrium?, The role of linkage disequilibrium in facilitating allelic association, What is a haplotype?, The importance of haplotypes, Haplotype tagging, The missing phase information problem, Haplotype determination options, Statistical estimation of haplotypes, General framework for case-control studies using haplotypes, Haplotype estimation and permutation testing, Statistical challenges, Software packages